# 证明

$\left[\alpha \cdot {x}_{1}^{n}+\beta \cdot {x}_{2}^{n}\right]=p\cdot \left[\alpha \cdot {x}_{1}^{n-1}+\beta \cdot {x}_{2}^{n-1}\right]+q\cdot \left[\alpha \cdot {x}_{1}^{n-2}+\beta \cdot {x}_{2}^{n-2}\right]$$[\alpha \cdot x_1^{n} +\beta \cdot x_2^{n}] = p\cdot [\alpha \cdot x_1^{n-1} +\beta \cdot x_2^{n-1}] + q\cdot [\alpha \cdot x_1^{n-2} +\beta \cdot x_2^{n-2}]$

$\left[\alpha \cdot {x}_{1}^{n}\right]+\beta \cdot {x}_{2}^{n}=\left[p\cdot \alpha \cdot {x}_{1}^{n-1}+q\cdot \alpha \cdot {x}_{1}^{n-2}\right]+p\cdot \beta \cdot {x}_{2}^{n-1}+q\cdot \beta \cdot {x}_{2}^{n-2}$$[\alpha\cdot x_1^{n}]+\beta\cdot x_2^{n}=[p\cdot \alpha \cdot x_1^{n-1}+q\cdot \alpha\cdot x_1^{n-2}]+p\cdot \beta\cdot x_2^{n-1}+q\cdot\beta \cdot x_2^{n-2}$

$\alpha \cdot {x}_{1}^{n}=p\cdot \alpha \cdot {x}_{1}^{n-1}+q\cdot \alpha \cdot {x}_{1}^{n-2}$$\alpha\cdot x_1^{n}=p\cdot \alpha \cdot x_1^{n-1}+q\cdot \alpha\cdot x_1^{n-2}$

$\beta \cdot {x}_{2}^{n}=p\cdot \beta \cdot {x}_{2}^{n-1}+q\cdot \beta \cdot {x}_{2}^{n-2}$$\beta\cdot x_2^{n}=p\cdot \beta\cdot x_2^{n-1}+q\cdot\beta \cdot x_2^{n-2}$

${x}_{1}^{n}=p\cdot {x}_{1}^{n-1}+q\cdot {x}_{1}^{n-2}$$x_1^{n}=p\cdot x_1^{n-1}+q\cdot x_1^{n-2}$

${x}_{2}^{n}=p\cdot {x}_{2}^{n-1}+q\cdot {x}_{2}^{n-2}$$x_2^{n}=p\cdot x_2^{n-1}+q\cdot x_2^{n-2}$

${x}_{1}^{2}=p\cdot {x}_{1}+q⇔{x}_{1}^{2}-p\cdot {x}_{1}-q=0$$x_1^2=p\cdot x_1+q \Leftrightarrow x_1^2-p\cdot x_1-q=0$

${x}_{2}^{2}=p\cdot {x}_{2}+q⇔{x}_{2}^{2}-p\cdot {x}_{2}-q=0$$x_2^2=p\cdot x_2+q \Leftrightarrow x_2^2-p\cdot x_2-q=0$

（不靠谱的证明到此结束）

# 用法案例：斐波那契数列

${F}_{0}={F}_{1}=1$$F_0 = F_1 = 1$

${F}_{n}={F}_{n-1}+{F}_{n-2}:n\ge 2$$F_n = F_{n-1}+F_{n-2}:n\geq2$

${x}^{2}-x-1=0$$x^2 - x -1=0$

${F}_{0},{F}_{1}$$F_0,F_1$带入通项公式。

${F}_{0}=\alpha +\beta =1$$F_0=\alpha+\beta=1$

${F}_{1}=\alpha \cdot \frac{1+\sqrt{5}}{2}+\beta \cdot \frac{1-\sqrt{5}}{2}=1$$F_1=\alpha\cdot\frac{1+\sqrt{5}}{2}+\beta\cdot \frac{1-\sqrt{5}}{2}=1$

$\alpha =\frac{\sqrt{5}+1}{2\sqrt{5}},\beta =\frac{\sqrt{5}-1}{2\sqrt{5}}$$\alpha=\frac{\sqrt{5}+1}{2\sqrt{5}},\beta=\frac{\sqrt{5}-1}{2\sqrt{5}}$

${F}_{1}=\alpha \cdot \frac{1+\sqrt{5}}{2}+\beta \cdot \frac{1-\sqrt{5}}{2}=1$$F_1=\alpha\cdot\frac{1+\sqrt{5}}{2}+\beta\cdot \frac{1-\sqrt{5}}{2}=1$

${F}_{2}=\alpha \cdot \left(\frac{1+\sqrt{5}}{2}{\right)}^{2}+\beta \cdot \left(\frac{1-\sqrt{5}}{2}{\right)}^{2}=1$$F_2=\alpha\cdot(\frac{1+\sqrt{5}}{2})^2+\beta\cdot (\frac{1-\sqrt{5}}{2})^2=1$

—> 百度百科戳这里 <—

• 广告
• 抄袭
• 版权
• 政治
• 色情
• 无意义
• 其他

120